The Effect Of Zumba Exercises Accompanied By A Suggested Diet On Weight Loss Improvement Of Some Anthropometric Measurements And Body Image In Overweight Women. - الروضي الاء; مجاهد مطهر عبد الغني (sports creativity, 2025)
To identify the effect of Zumba exercises accompanied by a proposed diet in losing weight and improving some anthropometric measurements and body image in overweight women. The research sample consisted of (10) women, who were deliberately selected from the research community. The researchers used the experimental method, due to its suitability to the nature of the research. The research results confirmed the achievement of the research hypothesis. The research concluded by presenting the most important recommendations, including the necessity of benefiting from Zumba exercises accompanied by diets in health and fitness centers